2021
DOI: 10.1097/md.0000000000026483
|View full text |Cite
|
Sign up to set email alerts
|

Association between pulmonary artery to aorta diameter ratio with pulmonary hypertension and outcomes in diffuse cystic lung diseases

Abstract: To investigate the importance of pulmonary vascular measurements on computed tomography (CT) in predicting pulmonary hypertension (PH) and worse outcomes in diffuse cystic lung diseases (DCLDs). We conducted a cross-sectional study of patients with DCLDs. Patients underwent pulmonary function tests, a six-minute walk test (6MWT), chest CT, transthoracic echocardiography, and right heart catheterization. Pulmonary artery (PA) diameter and PA-ascending aorta ratio (PA-Ao ratio) were obtained from CT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Another study showed that patients with cystic lung disease had a MAo diameter of 31 mm. 26 In our study, the diameter was 32.01 ± 3.14 mm in women and 32.39 ± 4.18 mm in men, with a mean value of 32.21 ± 3.71 mm. Our findings were consistent with the results of these previous studies 22 , 26 , 27 ; the MAo diameter increased in the patient groups compared to the control group in both genders.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…Another study showed that patients with cystic lung disease had a MAo diameter of 31 mm. 26 In our study, the diameter was 32.01 ± 3.14 mm in women and 32.39 ± 4.18 mm in men, with a mean value of 32.21 ± 3.71 mm. Our findings were consistent with the results of these previous studies 22 , 26 , 27 ; the MAo diameter increased in the patient groups compared to the control group in both genders.…”
Section: Discussionsupporting
confidence: 44%
“… 26 In our study, the diameter was 32.01 ± 3.14 mm in women and 32.39 ± 4.18 mm in men, with a mean value of 32.21 ± 3.71 mm. Our findings were consistent with the results of these previous studies 22 , 26 , 27 ; the MAo diameter increased in the patient groups compared to the control group in both genders. Ground-glass opacity, pulmonary consolidation, air bronchogram and airway changes, pulmonary vascular enlargement, reticular pattern and linear opacification, pleural effusion, and pulmonary thromboembolism are considered the main chest CT findings of COVID-19.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Usually, as pathology is defined the MPA/Ao asc ratio >0.9 [ 1 , 2 , 4 , 23 , 38 , 39 ], or up to >1.05–1.1 in some studies [ 3 , 20 ]. In severe PH, a high-risk situation for the development of complications is considered, when the MPA/Ao asc ratio exceeds 1.5–2 [ 8 , 28 , 40 ].…”
Section: Discussionmentioning
confidence: 99%